Предмет: Математика,
автор: AsIaNa
Разложить многочлен на множители: а) х^4 – 6х^ 3 + 13х ^2 - 12х + 4
б) х (y + z)^ 2 + y (z + x) ^2 +z (x+y)^ 2 - 4 x y z
Ответы
Автор ответа:
0
Разложить многочлены на множители:
а) х^4 – 6х^ 3 + 13х ^2 - 12х + 4
х=1 1^4 – 6(1^ 3 )+ 13(1 ^2) - 12(1) + 4 =1-6+13-12+4=0 ⇒
х^4 – 6х^ 3 + 13х ^2 - 12х + 4=(х-1)(х^ 3 - 5х ^2 + 8х - 4)
х=1 1^ 3 - 5(1 ^2) + 8(1) - 4=1-5+8-4=0 ⇒
х^4–6х^3+13х^2-12х+4=(х-1)(х^3-5х^2+8х-4)=(х-1)(х-1)(х^2-4х+4)=(х-1)²(х-2)² ⇔
х^4–6х^3+13х^2-12х+4=(х-1)²(х-2)²
б) х (y + z)^ 2 + y (z + x) ^2 +z (x+y)^ 2 - 4 x y z
а) х^4 – 6х^ 3 + 13х ^2 - 12х + 4
х=1 1^4 – 6(1^ 3 )+ 13(1 ^2) - 12(1) + 4 =1-6+13-12+4=0 ⇒
х^4 – 6х^ 3 + 13х ^2 - 12х + 4=(х-1)(х^ 3 - 5х ^2 + 8х - 4)
х=1 1^ 3 - 5(1 ^2) + 8(1) - 4=1-5+8-4=0 ⇒
х^4–6х^3+13х^2-12х+4=(х-1)(х^3-5х^2+8х-4)=(х-1)(х-1)(х^2-4х+4)=(х-1)²(х-2)² ⇔
х^4–6х^3+13х^2-12х+4=(х-1)²(х-2)²
б) х (y + z)^ 2 + y (z + x) ^2 +z (x+y)^ 2 - 4 x y z
Автор ответа:
0
х (y + z)^ 2 + y (z + x) ^2 +z (x+y)^ 2 - 4 x y z=х (y + z)^ 2 + (yz^2+2yxz+yx^2)+(zx^2+2zxy+zy^2) -4xyz=х (y+z)^2 + (yz^2 + yx^2) + (zx^2+zy^2)=х (y + z)^2+ (yz^2 +zy^2)+ (yx^2+zx^2)=х (y + z)^2+ yz(z +y)+ x^2(y+z)=(y+z)[x(y+z)+yz+x^2]=(y+z)[xy+xz+yz+x^2]
Похожие вопросы
Предмет: Геометрия,
автор: filatovamaria069
Предмет: Русский язык,
автор: Аноним
Предмет: Алгебра,
автор: gfvucydtsy
Предмет: Алгебра,
автор: Lindasayfitdin
Предмет: Алгебра,
автор: slavanikitin9